Innate Immune Responses to Highly Pathogenic Coronaviruses and Other Significant Respiratory Viral Infections - Ahmed-Hassan, Hanaa; Sisson, Brianna; Shukla, Rajni Kant; Wijewantha, Yasasvi; Funderburg, Nicholas T.; Li, Zihai; Hayes, Don; Demberg, Thorsten; Liyanage, Namal P. M. (Frontiers in Immunology, 2020)
The new pandemic virus SARS-CoV-2 emerged in China and spread around the world in less than three months, infecting millions of people, and causing countries to shut down public life and businesses. Nearly all nations were unprepared for this pandemic with healthcare systems stretched to their limits due to the lack of an effective vaccine and treatment. Infection with SARS-CoV-2 can lead to Coronavirus disease 2019 (COVID-19). COVID-19 is respiratory disease that can result in a cytokine storm with stark differences in morbidity and mortality between younger and older patient populations. Details regarding mechanisms of viral entry via the respiratory system and immune system correlates of protection or pathogenesis have not been fully elucidated. Here, we provide an overview of the innate immune responses in the lung to the coronaviruses MERS-CoV, SARS-CoV and SARS-CoV-2. This review provides insight into key innate immune mechanisms that will aid in the development of therapeutics and preventive vaccines for SARS-CoV-2 infection.